In Vitro Multiplication And Plant Regeneration Of Kiwano (Cucumis Metuliferus E. Mey. Ex Naudin), A Potential Super Nutritious Fruit - Lai, Chern Shun (2023)
Cucumis metuliferus is a plant of the same genus as cucumbers with spike-bearing fruits that are yellow to orange in colour. This plant originated from tropical Africa and is commonly used by native communities as food or medication. Recent studies conducted on this plant showed various positive pharmacological effects other than being a plant resistant to nematode infection. This super nutritious fruit is hardly available even though it possesses high market value. To overcome problems with availability, mass production, and quality planting materials, a reliable in vitro multiplication and regeneration protocol was established. Seed culture was successful with surface sterilization protocol of removing seed coat and swirling in 5% Clorox solution for 5 minutes. The germination rate was obtained at 76.6%. Shoot regeneration with various cytokinins showed that 5μM AdS promoted the tallest shoot growth at 5.56 ± 0.77cm per shoot. Combination treatment of 2.5μM mT + 5μM AdS produced taller shoots at 5.74 ± 0.65cm per shoot. This combination treatment was then applied to 6 types of LED treatments. Mint white light produced the tallest shoots at 4.06 ± 0.58cm, while white, blue, red, and red:blue (1:1) lights displayed similar results. Root regeneration was the best when auxins, IAA, IBA, and NAA were not added. Silver nanoparticles (AgNPs) did not improve the growth of shoots and also did not inhibit root growth.